Unusual Pathology in a Kidney from a Heart-Transplant Patient. (5th November 2017) - Larcher, Marie; Delas, Audey; Delmas, Clément; Cointault, Olivier; Dambrin, Camille; Del Bello, Arnaud; Kamar, Nassim
Abstract : Acute kidney injury (AKI) is often observed after heart transplantation. In this setting, acute tubular necrosis is the main histological finding on kidneys. We report the unusual pathology found in a kidney from a heart-transplant patient. The patient experienced several hemodynamic insults, massive transfusion, and implantation of a mechanical circulatory-support device before heart transplantation: there was prolonged AKI after transplantation. A kidney biopsy revealed acute tubular necrosis and renal hemosiderosis, which was probably related to the transfusion and to mechanical circulatory-support device-induced intravascular hemolysis. Assessment of iron during resuscitation could have prevented, at least partly, AKI.